2010
DOI: 10.1007/s10800-010-0234-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition: a versatile and inexpensive tool for the synthesis of nanoparticles, nanorods, nanowires, and nanoclusters of metals

Abstract: The synthesis of various nanoscale materials, such as nanoparticles, nanowires of Au, Pt, Ni Co, Fe, Ag etc., by electrodeposition techniques have been demonstrated in this article. Both potentiostatic and galvanostatic methods were employed to carry out the electrodeposition process under different potential ranges, time durations, and current densities. The electrochemical behavior of the deposited nanoparticles on various substrates was investigated by cyclic voltammetric and chronoamperometric techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(110 citation statements)
references
References 87 publications
1
106
0
3
Order By: Relevance
“…Since Pt nanostructures are commonly grown from solutions containing Pt 4? ions by spontaneous deposition, potentiostatic or pulsed electrodeposition and precipitation, there is a presumed reduction of Pt 4? ions to their metallic state in all of these synthesis routes as Pt atomic layers stack and grow [19]. In principle, SLRR growth is a window through which one can study the characteristics of the initial stages of deposition common to all of these techniques.…”
Section: Discussion 1: Film Characterizationmentioning
confidence: 99%
“…Since Pt nanostructures are commonly grown from solutions containing Pt 4? ions by spontaneous deposition, potentiostatic or pulsed electrodeposition and precipitation, there is a presumed reduction of Pt 4? ions to their metallic state in all of these synthesis routes as Pt atomic layers stack and grow [19]. In principle, SLRR growth is a window through which one can study the characteristics of the initial stages of deposition common to all of these techniques.…”
Section: Discussion 1: Film Characterizationmentioning
confidence: 99%
“…Many authors have studied different kinds methods to synthesize copper nanowires, including synthesis using template materials [1][2][3][4][5][6], solvothermal or hydrothermal [7,8], and wet synthesis [9][10][11][12][13]. Although the template technique produces a quite clean and straight copper nanowires, but the process requires cleaning the sacrificed materials which considered as a delicate and time-consuming process.…”
Section: Introductionmentioning
confidence: 99%
“…However, these are still used as powerful techniques to synthesize nanowire in the high crystalline ratio. The wet synthesis in producing copper nanowires had been explored by many authors using different capping agents and reductors [8][9][10][11][12][13]. Perhaps, the simplest and fastest in producing copper nanowire in wet synthesis is done using copper salt, N 2 H 4 (hydrazine) as a reductor, and an amine group as a capping agent such as done by Rathmell and his group [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In general, the chemical synthesis route is more developed than the electrochemical one, as it allows better control of the final type of NPs. 5,8,9 However, a number of studies have shown that it is also possible to control Au NPs morphology using electrochemistry, [10][11][12][13][14][15][16] although a lot of them use a gold sacrificial anode like source of gold ions. [13][14][15] Electrochemical synthesis offers important advantages such as the production of NPs with high purity.…”
Section: Introductionmentioning
confidence: 99%